2021
DOI: 10.2196/23765
|View full text |Cite
|
Sign up to set email alerts
|

Health Information Technology Use Among Persons With Self-reported Atherosclerotic Cardiovascular Disease: Analysis of the 2011-2018 National Health Interview Survey

Abstract: Background Atherosclerotic cardiovascular disease (ASCVD) is the leading cause of morbidity and mortality in the United States. Health information technologies (HITs) have recently emerged as a viable intervention to mitigate the burden of ASCVD. Approximately 60% of US adults report searching the internet for health information; however, previous research has not examined the prevalence of general technology or HIT use among adults with and without ASCVD. In addition, social determinants in HIT us… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 23 publications
2
13
0
Order By: Relevance
“…Findings indicate that among people with SPD, older age, male sex, lower education level, and lower income, were associated with lower odds of using DHT to interact with the healthcare system. These findings are consistent with previous research which suggests that trends in DHT use across the general population is increasing but disparities in DHT engagement still exist, which could potentially exacerbate health disparities 13,15 . The finding that individuals with higher education level and high-income high SES background are more likely to use DHT matches observations from past studies 16 .…”
Section: Discussionsupporting
confidence: 92%
“…Findings indicate that among people with SPD, older age, male sex, lower education level, and lower income, were associated with lower odds of using DHT to interact with the healthcare system. These findings are consistent with previous research which suggests that trends in DHT use across the general population is increasing but disparities in DHT engagement still exist, which could potentially exacerbate health disparities 13,15 . The finding that individuals with higher education level and high-income high SES background are more likely to use DHT matches observations from past studies 16 .…”
Section: Discussionsupporting
confidence: 92%
“…A complete extraction table of the studies may be found in Table S1 . 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 The study characteristics are summarized in Table 1 , the SDOH domains addressed by each study are summarized in Table 2 , and the primary uses of the SDOH data among each study are summarized in Table 3…”
Section: Resultsmentioning
confidence: 99%
“…Most studies used a cross‐sectional study design (n=17), retrospective cohort studies (n=13), and geographical and spatial analysis (n=12), whereas less common study designs included case studies (n=3), clinical trials (n=3), and randomized control trials (n=2). Thirty‐three studies used linear or logistic regression methods, 35 , 37 , 38 , 39 , 40 , 41 , 42 , 46 , 47 , 48 , 51 , 52 , 54 , 56 , 57 , 58 , 59 , 60 , 62 , 64 , 65 , 66 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 80 , 81 and 14 studies applied spatial analysis to understand the relationship between SDOH and CVD outcomes. 35 , 36 , 37 , 38 , 45 , 50 , 53 , 54 , 58 , 59 , 60 , 61 Machine learning, including data mining, gradient boosting machine, extreme gradient boosting, phase type random forests, Breiman's random forest, support vector machine, and tree‐based classification were used in 4 stu...…”
Section: Resultsmentioning
confidence: 99%
“…Aneurysms can occur anywhere in the body but are mostly seen in the aorta, the body's largest artery. Treatment options for aneurysms may include close monitoring, medication to control blood pressure, or surgery to repair or remove the affected vessel [16]. Stroke is another serious condition that may require vascular healthcare.…”
Section: Overviewmentioning
confidence: 99%